Architektura wiejska w granicach Prus Zachodnich jako przedmiot zainteresowań naukowych i konserwatorskich do lat 40. XX w. - Prarat, Maciej (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2014)
Rural architecture in West Prussia as a matter of interest of Conservation and Monument Studies until the 1940s The aim of this paper is to familiarize the readers with the activities undertaken by Prussian conservators in the subject of rural architecture in West Prussia. The earliest studies concerning rural architecture of Pomerania dated back to the fist half of the 19th century. Conservation activities were undertaken from the Elary 20th century. Several greater funds to renovate the farm buildings especially the arcaded houses in Żuławy were granted in the 1920s. Protection was also extender to the mills. Rural architecture was to symbolize the relations with German medieval settlement as well as guard the Germaness in the east. It was signifiant in terms of historical, landscape and monument values.